The holiday (2006) [videorecording (DVD)] - Meyers, Nancy; Diaz, Cameron; Winslet, Kate; Law, Jude, 1972-; Black, Jack (Sony Pictures Home Entertainment, 2007)
Amanda lives in Los Angeles and is a movie trailer editor. Iris lives in Surrey, England and is a journalist. The two live five thousand miles apart and have never met, but are dealing with the same problem: men. Amanda just broke up with her cheating boyfriend. Iris has pined for her ex. They both come upon a website that advocates home exchange and the two swap houses for two weeks at Christmas - both with a goal to forget their troubled love lives. Love ends up finding them anyways. Amanda starts a romance with Iris' older brother, Graham, a book editor and Iris starts a romance with a friend of Amanda's, movie composer Miles. With new-found romance, both their lives change forever.